Tingkat Kesukaan Sosis Sapi terhadap Extender Tahu - Eka Wahyu Nugroho; Roisu Eny Mudawaroch; Faruq Iskandar (Universitas Muhammadiyah Purworejo, 2021)
An extender is added to sausage ingredients to increase the density or modify the quality of the sausage. The main ingredients of this research are beef and tofu. This study was conducted using a completely randomized design method (CRD) with 4 treatments and a panel as a treatment replication. The data obtained were analyzed by Analysis Of Variance (ANOVA), followed by Duncan's New Multiple Rane Test (DMRT). The results of the analysis of variance in beef sausage with the use of tofu as an extender have a very significant effect on the average hedonic score and quality score on color. The average color quality score shows that it is not red, while the score is classified as very dislike. The results of the analysis of variance in beef sausage with the use of tofu as an extender have a very significant effect on the average hedonic score and quality score on the aroma. The average aroma quality score is very unscented while the hedonic aroma score indicates liking. The results of the analysis of variance in beef sausage with the use of tofu as an extender have a significant effect on the average hedonic score and quality score on texture. The mean texture score indicates chewy while the hedonic texture indicates liking. The results of the analysis of variance in beef sausage with the use of tofu as an extender have a very significant effect on the average hedonic taste score and taste quality score. The average taste quality score indicates feeling to know, while the hedonic taste score indicates liking. The conclusion of adding a different level of tofu extender shows that the addition of 10g of tofu as an extender to 490g of beef can increase the texture value of beef sausage, the addition of 30g of tofu as an extender to 470g of beef can increase the value of aroma and taste quality in beef sausage. It is suggested that the addition of 10g of tofu as an extension with 490g of beef can be used in making beef sausage.